Isomaltooligosaccharide-binding structure of Paenibacillus sp. 598K cycloisomaltooligosaccharide glucanotransferase. Issue 2 (28th April 2017) - Fujimoto, Zui; Kishine, Naomi; Suzuki, Nobuhiro; Suzuki, Ryuichiro; Mizushima, Daiki; Momma, Mitsuru; Kimura, Keitarou; Funane, Kazumi
Abstract : Paenibacillus sp. 598K cycloisomaltooligosaccharide glucanotransferase (CITase), a member of glycoside hydrolase family 66 (GH66), catalyses the intramolecular transglucosylation of dextran to produce CIs with seven or more degrees of polymerization. To clarify the cyclization reaction and product specificity of the enzyme, we determined the crystal structure of PsCITase. The core structure of PsCITase consists of four structural domains: a catalytic (β/α)8 -domain and three β-domains. A family 35 carbohydrate-binding module (first CBM35 region of Paenibacillus sp. 598K CITase, (PsCBM35-1)) is inserted into and protrudes from the catalytic domain. The ligand complex structure of PsCITase prepared by soaking the crystal with cycloisomaltoheptaose yielded bound sugars at three sites: in the catalytic cleft, at the joint of the PsCBM35-1 domain and at the loop region of PsCBM35-1. In the catalytic site, soaked cycloisomaltoheptaose was observed as a linear isomaltoheptaose, presumably a hydrolysed product from cycloisomaltoheptaose by the enzyme and occupied subsites –7 to –1. Beyond subsite –7, three glucose moieties of another isomaltooiligosaccharide were observed, and these positions are considered to be distal subsites –13 to –11. The third binding site is the canonical sugar-binding site at the loop region of PsCBM35-1, where the soaked cycloisomaltoheptaose is bound. The structure indicated that the concave surface between the catalytic domain and PsCBM35-1 plays a guiding route for the long-chained substrate at the cyclization reaction.